Temporal variation of surface chlorophyll a in the Romanian near-shore waters - VASILIU, D.; BOICENCO, L.; GOMOIU, M.T.; LAZAR, L.; MIHAILOV, M.E. (Mediterranean Marine Science, 2012)
Chlorophyll a (Chl a) dynamics in the near-shore waters of the NW Black Sea was investigated between 2002 and 2010 in the Mamaia Bay (north of Constanta, Romania) in relation to some physical-chemical parameters. Chl a ranged from values below detection limit (0.17 μg.l–1) to 76.13 μg.l–1, and showed large temporal variability (CV = 142.3%), strongly related to the Danube’s discharges, meteorological conditions, and anthropogenic pressures. Seasonally, Chl a showed a winter/early spring maximum, sometimes followed by a stronger one in April/early May, closely linked to the Danube’s higher discharges in spring. After significantly lower concentrations in late spring/early summer, Chl a exhibited its strongest maximum in summer (July-August), followed by another one in autumn (late September–October). Interannual variation of Chl a seems to be controlled by the hydrometeorological conditions in summer. Thus, the highest annual Chl a means were observed in 2006 (8.56 ± 8.35 μg.l–1) and 2010 (9.20 ± 11.72 μg.l -1), when, also, the summer Chl a concentrations were maximal due to the large riverine discharges. The lowest annual Chl a mean was observed in 2004 (4.57 ± 9.81μg.l–1), closely linked to minimal summer Chl a resulted from a strong P limitation during summertime.